PERAN LEMBAGA PEMASYARAKATAN DALAM MEMENUHI HAK-HAK NARAPIDANA PENYANDANG DISABILITAS - Subroto, Mitro; Jabo, Yunan Fariz (Ensiklopedia of Journal, 2024)
Abstract: This research explores the role of correctional institutions in fulfilling the rights of incarcerated individuals with disabilities. The urgency of this study arises from the increasing recognition of the need for equitable treatment and access to services for disabled inmates, which remains underexplored. Utilizing a qualitative approach, data were collected through interviews with prison staff and disability advocates, alongside a review of relevant policies. The findings indicate significant gaps in awareness and implementation of disability rights within correctional facilities, highlighting the necessity for systemic changes to ensure compliance with legal standards and improve the living conditions of disabled inmates. This study contributes to the discourse on human rights in correctional settings and advocates for enhanced support systems. Keywords: correctional institutions; disability rights; incarcerated individuals; human rights; systemic change.